Prevalence of Tobacco-Associated Oral Mucosal Lesions in Patients Visiting a Tertiary Hospital of Chitwan, Nepal - Ghosh, Snehashish; Dhungel, Safal; Bhattarai, Rosina; Mahanta, Swagat Kumar (Nepal Journal of Health Sciences, 2024)
Introduction: Tobacco consumption in different forms is one of the biggest risk factors for the emergence of oral mucosal lesions (OML), including precancer and oral cancer. The habit’s type and duration affect the nature and location of tobacco-associated OML. Objectives: The objective of this study is to estimate the prevalence of tobacco-associated OML among patients visiting the dental outpatient department of a tertiary care hospital in Chitwan, Nepal. Methods: A descriptive, cross-sectional study was done among 1666 patients visiting the dental outpatient department. Data collection was performed through personal interviews and clinical examination. Data was entered in MS Excel (2019) and analysis was performed using SPSS Version 22. Pearson’s chi-square test was done to see the association between variables. Results: Among 1666 subjects, 516 (30.97%) were tobacco users. Among the tobacco users, 247 (47.86%) were males and 269 (52.13%) were females. Among 516 tobacco users, tobacco-associated oral mucosal lesions (OML) were present in 98(18.99%) individuals. Leukoplakia was the most prevalent tobacco-associated OML among smokers, whereas tobacco-pouch keratosis was among tobacco chewers. Conclusion: The results of the present study can be used as a reference to identify vulnerable groups of people and devise awareness campaigns and cessation programs that can motivate the population to quit tobacco.